Advances in conceptual modeling : ER 2013 Workshops, LSAWM, MoBiD, RIGiM, SeCoGIS, WISM, DaSeM, SCME, and PhD Symposium, Hong Kong, China, November 11-13, 2013, Revised Selected Papers - Chiu, Dickson; Parsons, Jeffrey (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of workshops, held at the 32nd International Conference on Conceptual Modeling, ER 2013, in Hong Kong, China in November 2013. The 30 revised full papers were carefully reviewed and selected out of 57 submissions. The papers are organized in sections related to the individual workshops: LSAWM, Legal and Social Aspects in Web Modeling; MoBiD, 1st International Workshop on Modeling and Management of Big Data; RIGiM, 5th International Workshop on Requirements, Intentions and Goals in Conceptual Modeling; SeCoGIS, 7th International Workshop on Semantic and Conceptual Issues in Geographic Information Systems; WISM, 10th International Workshop on Web Information Systems Modeling; DaSeM, Data Mining and Semantic Computing for Object Modeling; SCME, 1st Symposium on Conceptual Modeling Education; and PhD Symposium. Continuing the ER tradition, the ER 2013 workshops provided researchers, students, and industry professionals with a forum to present and discuss emerging, cutting-edge topics related to conceptual modeling and its applications.